2015
DOI: 10.1002/chem.201500868
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Antioxidant Properties of Dextran‐Coated Redox Active Nanoparticles Due to Synergetic Photoreduction–Oxidation

Abstract: Nanoparticles have proven to be novel material with resourceful applications in the field of nanomedicine. Cerium oxide nanoparticles (CNPs) coated with dextran (Dex-CNPs) have been shown to exhibit anticancer properties which is attributed to the change in oxidation states mediated at the oxygen vacancies on the surface of CNPs. In this study, the extreme sensitivity of Dex-CNPs to visible light is demonstrated using room light with a clear indication of synergetic phenomenon of photoreduction of CNPs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…The chemical properties of CNPs, such as, its surface chemistry regulated by the surface Ce 3+ /Ce 4+ ratio can significantly modulate the bioactivity and antioxidant property of CNPs. 12,15,16 We note that the protein corona formation in the biologically relevant media is regulated by the physical property – dispersion stability as well as by the presence of any chemical entity on CNPs, thereby deciding their cellular internalization. 7, 17 Therefore, it is necessary to thoroughly characterize and analyze the role of chemical entities that are present on the surface of CNPs, after the synthesis and prior to their use in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical properties of CNPs, such as, its surface chemistry regulated by the surface Ce 3+ /Ce 4+ ratio can significantly modulate the bioactivity and antioxidant property of CNPs. 12,15,16 We note that the protein corona formation in the biologically relevant media is regulated by the physical property – dispersion stability as well as by the presence of any chemical entity on CNPs, thereby deciding their cellular internalization. 7, 17 Therefore, it is necessary to thoroughly characterize and analyze the role of chemical entities that are present on the surface of CNPs, after the synthesis and prior to their use in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our work has provided evidence that the synthesis method and the chemistry between precursors play an equally important role in determining the physio-chemical characteristics and bioactivity of CNPs. 7, 12, 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that nanoceria can act both as superoxide dismutase (SOD), by neutralizing superoxide radicals, and catalase (CAT), by promoting the decomposition of hydrogen peroxide into water and oxygen. 44 According to the literature, an increase in Ce 3+ /Ce 4+ ratio induces mimetic properties to Si-Fulp/ceria which are more similar to SOD than CAT. 44 The O 1s spectrum of ( Fig.…”
Section: Fwhmmentioning
confidence: 99%